Reducing Superfluous Opioid Prescribing Practices After Brain Surgery: It Is Time to Talk About Drugs. Issue 1 (16th April 2021) - Asmaro, Karam; Fadel, Hassan A; Haider, Sameah A; Pawloski, Jacob; Telemi, Edvin; Mansour, Tarek R; Chandra, Ankush; Bazydlo, Michael; Robin, Adam M; Lee, Ian Y; Air, Ellen L; Rock, Jack P; et al.
Abstract: BACKGROUND: Opioids are prescribed routinely after cranial surgery despite a paucity of evidence regarding the optimal quantity needed. Overprescribing may adversely contribute to opioid abuse, chronic use, and diversion. OBJECTIVE: To evaluate the effectiveness of a system-wide campaign to reduce opioid prescribing excess while maintaining adequate analgesia. METHODS: A retrospective cohort study of patients undergoing a craniotomy for tumor resection with home disposition before and after a 2-mo educational intervention was completed. The educational initiative was composed of directed didactic seminars targeting senior staff, residents, and advanced practice providers. Opioid prescribing patterns were then assessed for patients discharged before and after the intervention period. RESULTS: A total of 203 patients were discharged home following a craniotomy for tumor resection during the study period: 98 who underwent surgery prior to the educational interventions compared to 105 patients treated post-intervention. Following a 2-mo educational period, the quantity of opioids prescribed decreased by 52% (median morphine milligram equivalent per day [interquartile range], 32.1 [16.1, 64.3] vs 15.4 [0, 32.9], P < .001). Refill requests also decreased by 56% (17% vs 8%, P = .027) despite both groups having similar baseline characteristics. There was no increase in pain scores at outpatient follow-up (1.23 vs 0.85, P = .105). CONCLUSION: A dramatic reduction in opioids prescribed was achieved without affecting refill requests, patient satisfaction, or perceived analgesia. The use of targeted didactic education to safely improve opioid prescribing following intracranial surgery uniquely highlights the ability of simple, evidence-based interventions to impact clinical decision making, lessen potential patient harm, and address national public health concerns. Graphical Abstract: